Capacity to engage: studying role of individual differences in work engagement – evidences from Iran. Issue 9 (10th October 2016) - Ghorbannejad, Parisa; Esakhani, Ahmad
Abstract : Purpose: The purpose of this paper is to study the role of individual differences in employees' work engagement. More specifically, the paper explains how self-efficacy, proactive personality and conscientious traits determine work engagement. Design/methodology/approach: A quantitative approach was used. Data for this study were collected from a manufacturing company via questionnaires. Participants were selected by classified sampling method and 305 questionnaires distributed among participants. In total, 263 respondents completed the questionnaires. Findings: The findings show that all individual traits influence employees' work engagement. But, the extent of their influence is not equal. Results of this study showed that various individual differences have different capacities for engaging employees. People who have more general self-efficacy are more likely to experience and report work engagement. Employees with conscientiousness trait have capacity to be engaged as well but to a lesser extent. Research limitations/implications: This study is a quantitative study. Data are collected from the automotive manufacturing industry. All respondents were technical experts with at least BA or BS degrees. This sample creates limitations in generalizing of the findings to broader and more representative populations. A more extensive study covering other industries and other traits is necessary to explore the relationships studied here. Practical implications: This study identifies various management strategies that could be used to increase employee work engagement. These strategies could be useful for managers in other organizational settings as well. Originality/value: There is an extensive body of literature in work engagement. Most of the research has been done in a framework of job demands-resources model. But this study was the first to study the effect of individual differences on work engagement in Iran.